PERAN SUSTAINABILITY REPORT SEBAGAI ANTESEDEN TERHADAP MANAJEMEN LABA DAN PENGARUHNYA PADA COST OF EQUITY (Studi Empiris Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2013 - 2016) - Risti Hanifah Hanifah; Abdul Rohman; Puji Harto (BBM (Buletin Bisnis & Manajemen), 2018)
This study aims to examine empirical evidence on the role of sustainability report as an antecedent variable to earnings management, tthrough discretionary accruals and cost of equity that is performed on companies listed on the Exchange Indonesia Securities in 2013-2016.The sample in this study using non-financial companies with a total sample of 78 selected companies with purposive sampling as sampling technique. This study uses Partial Least Squares (PLS) based on variance as a measuring instrument. The data obtained were analyzed by using is WarpPLS 5.0 application.Based on finding shows the importance of sustainability report role seen from each aspect in its influence to earnings management and cost of equity in company. Be concluded that sustainability report consisting of economics and social aspects have a positive effect on earnings management, while the environmental aspects negative affect on earnings management, earnings management have a negative effect on cost of equity and earnings management have a negative effect on cost of equity with the company size as a control variabel.